Acute fibrinous and organizing pneumonia following the COVID-19 mRNA-1273 vaccine. Issue 5 (14th November 2022) - Nevison, Stephanie; Hwang, David; Oikonomou, Anastasia; Fidler, Lee
Abstract: A 57-year-old man developed respiratory symptoms 72 hours after receiving his third dose of the COVID-19 mRNA-1273 vaccine and underwent computed tomography (CT) chest imaging. This showed new diffuse subpleural and peribronchovascular nodular opacities with reverse halo sign. Laboratory investigations demonstrated an eosinophil count of 0.8 x 10E9/L and unremarkable connective tissue disease screen. Bronchoscopy with lavage and transbronchial biopsies demonstrated lymphocytic alveolitis without evidence of infection and histopathology consistent with acute fibrinous and organizing pneumonia (AFOP). He was treated with corticosteroids resulting in resolution of symptoms and CT findings. We present radiographic and histopathologic findings of AFOP following COVID-19 mRNA-1273 vaccination.